In the Shadow of the Mountain: Assessing early impacts on community development from two mining prospects in South Greenland. Issue 2 (April 2019) - Hansen, Anne Merrild; Johnstone, Rachael Lorna
Highlights: Extractive projects have impacts on local communities at very early stages. Uncertainty and delay exacerbate social impacts. Risk and uncertainty can trigger feelings of powerlessness and paralysis. Social division caused by extractive projects is a cost to the community. Strategic planning should aim to instill confidence and a sense of control. Abstract: The study presented in this paper explored how people in South Greenland perceive their future prospects and the role of mining in this regard. This region hosts two important mining projects still in relatively early stages. The study further investigated how mining projects influence local decisions about individual and community development. It was conducted as a case study of the two specific mining projects and how these projects connect with local people's visions for the future and how people find that the projects influence the possibility of realizing these futures. The study is based on qualitative interviews with people from the towns of Narsaq and Qaqortoq and from a sheep farm near Narsaq, during a fieldtrip in May 2017. The authors found that the mining projects, even though they are still in the exploration phase, have already had great impact on local expectations for future development and on decision-making and planning in people's daily lives and thereby the development of the communities. Further, although located relatively close together in the same region, there are significant differences between the towns and their relations to the neighboring mining projects. There is both support and opposition towards the projects, which triggers division between individuals, between groups and between the towns. However, all agree on a need for more transparent processes and for timelines to inform people of when they can expect decisions to be made and activities to take place.